Boundary layer flow over elastic surfaces and combined method of drag reduction - Babenko, Viktor V. (Butterworth-Heinemann, 2012)
While other methods of drag reduction are well-known in marine R&D and ship design environments worldwide, compliant coating drag reduction remains less well-known and poorly understood. This important book presents cutting-edge techniques and findings from research sources not generally accessible by Western researchers and engineers, aiding the application and further development of this potentially important technology. Beginning with an introduction to drag reduction that places the authors work on elastic surfaces and combined techniques in context, the book moves on to provide a comprehensive study of drag reduction through elastic coating with both flow and material properties considered.